The search for life continued : planets around other stars - Jones, Barrie William (Springer-Praxis books in popular astronomy., 2008)
At present we have evidence only of life on Earth. New instruments and techniques are being developed not only to detect exoplanetary systems but that are also capable of analyzing the environments on discovered exoplanets to tell us whether a plan is habitable, and even inhabited.